Evaluation of IR and Raman spectroscopic markers of human collagens: Insides for indicating colorectal carcinogenesis - Synytsya, Alla; Janstová, Daniela; Šmidová, Miroslava; Synytsya, Andriy; Petrtýl, Jaromír (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2023)
Vibrational spectroscopic methods are widely used in the molecular diagnostics of carcinogenesis. Collagen, a component of connective tissue, plays a special role as a biochemical marker of pathological changes in tissues. The vibrational bands of collagens are very promising to distinguish between normal colon tissue, benign and malignant colon polyps. Differences in these bands indicate changes in the amount, structure, conformation and the ratio between the individual structural forms (subtypes) of this protein. The screening of specific collagen markers of colorectal carcinogenesis was carried out based on the FTIR and Raman (λex 785 nm) spectra of colon tissue samples and purified human collagens. It was found that individual types of human collagens showed significant differences in their vibrational spectra, and specific spectral markers were found for them. These collagen bands were assigned to specific vibrations in the polypeptide backbone, amino acid side chains and carbohydrate moieties. The corresponding spectral regions for colon tissues and colon polyps were investigated for the contribution of collagen vibrations. Mentioned spectral differences in collagen spectroscopic markers could be of interest for early ex vivo diagnosis of colorectal carcinoma if combine vibrational spectroscopy and colonoscopy.
Keywords: FTIR spectroscopy; Colorectal Neoplasms; kolonoskopie; Collagen; kolorektální nádory; Colonoscopy; lidé; Colorectal carcinoma; kolagen; Raman spectroscopy; Human collagens; Spectrum Analysis, Raman; Carcinogenesis; Ramanova spektroskopie; Humans